(Re)Constitution of the mathematics teacher's professional practice - Eduardo Pereira de Oliveira Rossa; Everton José Goldoni Estevam (Instituto Federal de Mato Grosso, 2022)
This bibliographic study aims to investigate aspects that influence the constitution and modification of the mathematics teachers' practice. By carrying out two searches on the Capes Periodicals Portal, one with the terms future teacher and mathematics and the other with teacher practice and mathematics, 24 articles were selected whose inductive analysis of keywords and objectives gave rise to three themes: i) Pre-service and In-service teacher education; ii) Collaborative environments; and iii) Didactic and technological resources. The results suggest that collaborative environments, in which teachers and prospective teachers can interact and share knowledge, beliefs and experiences, compose the essence of the processes of constitution and change of the teacher's practice. It is concluded, therefore, that collaborative actions should be promoted in the initial and continuing education of Mathematics teachers, because they allow us to rethink aspects of teaching practice and the very meaning of Mathematics, in a social perspective of professional teaching learning.